Empathy, knowledge, and personal. distress as correlates of HIV-/ AIDS-related stigmatization and discrimination (2010)
This study investigated the influence of empathy, knowledge, and personal distress on HIV/AIDS-related stigmatization and discrimination in a normal population ,(N = 346). Participants ranging' in age from 18 to 69 years responded to a validated questionnaire. The results showed a significant main and joint influence of empathy, knowledge, and personal distress on stigmatization and discrimination. Stigmatization and discrimination are thus identified as great obstacles in the fight against and, prevention of HIV/AIDS. Stakeholders in the HIV/AIDS arena should embark on mass education to increase knowledge of HIV/AIDS; also attitudinal change programs should be initiated, while health institutions should be effectively monitored to ensure best practices.